MAGALHÃES, Antonio Carlos de Melo. Religião: crítica e criatividade. São Paulo: Fonte Editorial, 2012. - Lopes, Marcelo; Huff Júnior, Arnaldo Érico (TEOLITERARIA - Revista de Literaturas e Teologias, 2017)
Trata-se de uma resenha da obra em tela.